2007
DOI: 10.1146/annurev.soc.33.040406.131743
|View full text |Cite
|
Sign up to set email alerts
|

From the Margins to the Mainstream? Disaster Research at the Crossroads

Abstract: The sociology of disasters has developed in ways that have weakened its ties with mainstream sociology. It has remained remarkably resistant to changes in the broader sociological landscape, and its strong applied focus has been a barrier to theoretical innovation. This situation is changing, as indicated by critiques of traditional ways of conceptualizing and explaining disasters; greater acceptance of constructivist formulations; willingness to acknowledge that disasters are accompanied by both social solida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
244
0
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(264 citation statements)
references
References 42 publications
2
244
0
12
Order By: Relevance
“…As suggested by Tierney (2007), the relationship between disasters and disorder was much more nuanced than it first appeared. Considerations of crime across an urban area, for example, might actually have missed variation across neighborhoods and types of crime.…”
Section: Disasters and Crime: Prior Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…As suggested by Tierney (2007), the relationship between disasters and disorder was much more nuanced than it first appeared. Considerations of crime across an urban area, for example, might actually have missed variation across neighborhoods and types of crime.…”
Section: Disasters and Crime: Prior Researchmentioning
confidence: 99%
“…The precise social impact of disasters remained somewhat unclear; some research suggested disasters have a destructive effect on the social fabric thereby causing "anomic" conditions such as looting (see Drabek, 2007;Quarantelli & Dynes, 1970;Tierney, 2007). Other theoretical frameworks suggested quite the opposite, where such events had a cohesive effect that drew communities together (see Miller, 2007;Quarantelli & Dynes, 1970.…”
Section: The Human Response To Disastermentioning
confidence: 99%
See 1 more Smart Citation
“…However, disaster research has predominantly focused on the post-disaster phase of recovery and mixed findings exist on how the existing social process of cohesion and informal social control, or collective efficacy, are influenced by the disaster itself. Tierney (2007) and Freudenburg (1997) argue that in order to better understand the effects of all types of disasters on social processes, communities, and individuals, disaster research needs to engage with the sociological literature on collective behavior, social capital and the social structure. Accordingly, the current study engages with the criminological literature on collective efficacy, a combination of perceived social cohesion and informal social control and its individual drivers, to better understand how a natural disaster influences how individuals perceive collective efficacy in their community after a major natural disaster.…”
Section: Corrosive and Therapeutic Effects Of Disastersmentioning
confidence: 99%
“…Such an investigation is important, primarily because the more general sociological literature has not extensively examined the extent to which perceptions of collective efficacy may change over time (Tierney, 2007). Further, there has been even less sociological examination of how these perceptions are influenced by major and sudden changes in the social environment.…”
Section: Introductionmentioning
confidence: 99%